Online Hoaxes, Existential Threat, and Internet Shutdown: A Case Study of Securitization Dynamics in Indonesia - Antony Lee (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
As one of the countries in the world with the highest growth of internet users, Indonesia is experiencing a rapid growth in social media usage. Some use social media for networking but some others use it to spread hoaxes, fake information, or disinformation. During presidential election in Indonesia in the period from 2017 to 2019, hoaxes and disinformation were widely circulated through social media and instant messaging. This phenomenon has triggered heated public debates on the nexus between digital spaces and security, which include how the online disinformation has threatened Indonesian security. For example, hoaxes were represented in the public sphere as an existential threat to Indonesian unity. Immediate question regarding this phenomenon is:why are online hoaxes and fake information represented in public spheres as a security threat? This paper argues that as a response toward the increase of online hoaxes, there were securitizing moves made by political elites and special agencies in Indonesia before and in the aftermath of the 2019 Indonesian presidential election. Employing discourse analysis of selected relevant news articles around the period of 2017-2019, this paper analyses the dynamic of the securitization of online hoaxes in Indonesia. Grounded within Securitization Theory, this paper analyses; the facilitating condition; the triumvirates of securitizations, which are the securitizing actors, the threats posed by hoaxes, and the audiences; as well as extraordinary measures executed to handle the threats; internet throttling and internet shutdown when necessary.